Idiopathic Aqueductal Stenosis: Late Neurocognitive Outcome in ETV Operated Adult Patients - Martinoni, Matteo; Miccoli, Giovanni; Riccioli, Luca Albini; Santoro, Francesca; Bertolini, Giacomo; Zenesini, Corrado; Mazzatenta, Diego; Conti, Alfredo; Cavallo, Luigi Maria; Palandri, Giorgio (Frontiers in Neurology, 2022)
Objective The aim of the present study is to evaluate neurocognitive outcome in patients affected by late onset idiopathic aqueductal stenosis (LIAS) who underwent endoscopic third ventriculostomy (ETV). Material and Methods A prospective study was conducted between January 2015 and December 2017 in a series of 10 consecutive adult patients referred to the Neurosurgery Department of IRCCS Istituto delle Scienze Neurologiche di Bologna, Bologna, Italy. All the adult patients admitted with absence of CSF flow through the aqueduct in phase-contrast (PC) – MRI sequences or turbulence void signal in T2 – weighted images in midsagittal thin-slice MR sequences underwent a specific neuroradiological, neurological and neurocognitive assessment pre- and postoperatively. Results All patients affected by gait and sphincter disturbances improved after ETV. Attentive and executive functions as well as visuo-spatial memory and verbal executive functions improved in several patients. Similarly, the affective and behavioral scales improved in almost 50% of the patients. No major complications have been recorded and no patients required a second surgery for shunt placement. Conclusion Endoscopic third ventriculostomy represents a safe and effective surgical procedure for the treatment of LIAS. In addition to neurological improvement, we demonstrated also postoperative neurocognitive improvement mainly in attentive and executive functions, visuo-spatial memory, verbal executive functions and behavioral and affective domains.